Comparison of properties of polyclonal anti-N-acetylchitooligosaccharides and anti-chitooligosaccharides antibodies produced for ELISA - Shim, YY; Shon, DH; Kwak, Y; Yu, J; Chee, KM (KOREAN SOC MICROBIOLOGY & BIOTECHNOLOGY, 2004)
To develop the enzyme-linked immunosorbent assay (ELISA) for the analysis of N-acetylchitooligosaccharides (NACOS) and chitooligosaccharides (COS), specific antibodies (Abs) were produced, and their properties were compared. N-acetylchitohexaose (NACOS6), chitohexaose (COS6), and COS mixture (COSM) conjugated to bovine serum albumin (BSA) were used to immunize rabbits. By the use of specific Abs and NACOS6-horseradish peroxidase (HRP), COS6HRP, and COSM-HRP conjugates, competitive direct ELISA (cdELISA) was developed. The detection limits of NACOS6 by the anti-NACOS6 Ab and COS6 by the anti-COS6 and the anti-COSM Abs in the cdELISAs were about 0.2, 2, and 2 ng/ml (ppb), respectively. In the cdELISA, the anti-NACOS6 Ab was found to recognize NACOS3-NACOS6, but not N-acetyl-D-glucosamine (GlcNAc), NACOS2, and COSs; the anti-COS6 Ab recognized COS2-COS6 and COSM, but not glucosamine (GlcN) and NACOSs. The recognition pattern of the anti-COSM Ab was almost the same as that of the anti-COS6 Ab, except that the former recognized COS2 and COS3 slightly better than the latter.
Keywords: LINKED-IMMUNOSORBENT-ASSAY; FUSARIUM-SOLANI; CHITOSAN; ENZYME; CHITIN; ACETYLCHITOHEXAOSE; CHITOHEXAOSE; GLUCOSAMINE; ANTIFUNGAL; GROWTH